PERHITUNGAN PSAK 23 (PENDAPATAN OPERASIONAL , NON OPERASIONAL) DAN PELAPORAN KEUANGAN PERUSAHAAN PADA PT JASA MARGA (PERSERO) TBK - Achmad Fauzi (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2018)
PSAK number 23 is described and explained about revenue recognition that can be used for companies. The collection method in this study is a qualitative research method with case studies. Implementation of operational, non-operational, and application revenue recognition with the Company's financial statements. PT Jasa Marga uses the cash basis method as a basis for revenue recognition, revenue is only calculated based on cash receipts and disbursements, with basic cash usage. PT Jasa Marga implements Minimum Service Standards (SPM) to obtain normal income and activities carried out by the company can run well.